2017
DOI: 10.1155/2017/1286246
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Transplantation: A Bioethical Lens

Abstract: Hematopoietic stem cell transplantation (HSCT) is one of a range of therapeutic options available to patients suffering from various diseases. HSCT procedure involves important ethical and legal aspects that can occur at every phase of the procedure: the clinical choice of whether to perform the procedure, pretransplantation preparation regimens, donor selection, stem cell harvest procedure, transplantation phase, and short-term and long-term follow-up care. In this discussion paper, we outline the ethical iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 96 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…HSCT is an expensive procedure [12] and even though the cost is substantially lower in countries like Mexico [9], it still represents a financial challenge for most patients, especially when one-half of the population is vulnerable and lives in poverty. Numerous studies have suggested that SES influences health outcomes associated with cancer incidence and mortality [13].…”
Section: Discussionmentioning
confidence: 99%
“…HSCT is an expensive procedure [12] and even though the cost is substantially lower in countries like Mexico [9], it still represents a financial challenge for most patients, especially when one-half of the population is vulnerable and lives in poverty. Numerous studies have suggested that SES influences health outcomes associated with cancer incidence and mortality [13].…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic stem cell transplantation (HSCT), either autologous or allogeneic, is an intensive therapy for patients who suffer from refractory or relapsing neoplastic disease and non-neoplastic genetic disorders 1,2 . Global, the rate of allogeneic HSCT continues to increase such that about 50,000-60,000 transplantation was performed annually.…”
Section: Application Of Latent Class Analysis In Diagnosis Of Graft-vmentioning
confidence: 99%
“…Loss to follow-up and non-adherence to long treatments are common, frequently due to misconceptions about the disease course (i.e. remission perceived as a definitive cure) or inability to adhere to follow-up due to the fear of job loss [13,14]. Finally, nonfamiliarity with the medical model of the hosting countries may impede long-term maintenance of treatment [13,14].…”
Section: Practical Barriers To Successful Donation and Transplantationmentioning
confidence: 99%